Disinfection of synthetic municipal wastewater effluent by pulsed UV-light treatment - Uslu, Gulsad; Demirci, Ali; Regan, John M. (American Society of Agricultural and Biological Engineers, 2013)
Disinfection of municipal wastewater is one of the most critical and urgent topics for water pollution control. Until recent years, chlorination has been the most common disinfection method for municipal wastewater. However, excessive chlorination causes harmful side-effects to both human and environmental health. Therefore new disinfection technologies have been investigated recently, such as pulsed UV-light. For water disinfection, conventional UV-light technology is actually not new; it is based on continuous-wave mercury vapor lamps in either low pressure (monochromatic at 253.7 nm) or medium pressure (polychromatic in the UV and visible light range), which requires long treatment times due its low energy output. Therefore, Pulsed UV-light (PUV) technology has been developed as a novel technology and proposed as an alternative to chlorine and conventional UV light for inactivation of pathogenic and spoilage microorganisms. This study was undertaken to quantify the efficacy of PUV for inactivation of Escherichia coli and Bacillus subtilis in synthetic municipal wastewater effluent. The effect of time (number of pulses), shelf height (distance from pulsed UV lamp), and volume of solution (depth) on log reduction of E. coli and B. subtilis by pulsed UV systems in synthetic municipal wastewater was investigated. The results demonstrated that complete inactivation was obtained after 15-s treatment at 8 cm shelf height, and 30 ml solution volume for E. coli and 15-s treatment at 8 cm shelf height and 15 ml solution volume for B. subtilis. In addition, a 2.5-25% (v/v) E. coli or B. subtilis inoculum was added to the synthetic municipal wastewater effluent and treated by pulsed UV-light for 5-45 s. Results showed that pulsed UV treatment at the optimum conditions increased suspended solids removal by 26.5% and 21.45% for E. coli and B. subtilis, respectively. Overall, the results of this study clearly demonstrated the complete inactivation of vegetative cells or spores in municipal wastewater effluents and further demonstrated the reduction of suspended solids, suggesting that pulsed UV-light has the potential to be used for disinfection of municipal wastewater effluent.
American Society of Agricultural and Biological Engineers Annual International Meeting 2013 -- 21 July 2013 through 24 July 2013 -- Kansas City, MO -- 98427
Keywords: B.subtilis; E. coli; Inactivation; Pulsed UV; Sanitation; Wastewater